An applied research agenda for navigating diverse livelihood challenges in rural coastal communities in the tropics - Diedrich, Amy; Duce, Stephanie; Eriksson, Hampus; Govan, Hugh; Harohau, Daykin; Koczberski, Gina; Lau, Jacqueline; Mills, David; Minter, Tessa; Steenbergen, Dirk; Troell, Max (Elsevier, 2022)
Rural, tropical coastal communities are experiencing sustained, often increasing food insecurity, poverty, and global change impacts. These challenges have stimulated a rise in projects aiming to enhance and diversify local livelihoods. The ability of these projects to achieve broad-scale benefits is limited by approaches that do not account for feedbacks among sectors and across marine and terrestrial environments. To address these limitations, we present an applied research agenda to support an integrated approach to livelihood project planning and management. This agenda explicitly examines interactions among natural resources, industries, and livelihoods and is based on three foundational activities: (1) a governance review and assessment, (2) strategic partnership formation, and (3) a diagnostic approach supported by science and shared outcomes. We add structure to the established logic in our field by broadening the sectoral and spatial scope of livelihoods projects, so they can better contribute to interrelated UN Sustainable Development Goals.